Technological innovations and the transformation of economic sectors: A concise overview of issues and concepts - Ulrich Dolata (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2017)
The paper examines two main questions: First, how are economic sectors changing under the influence of new technological opportunities that bear an enormous potential for development and deployment for them? And second, how might this kind of sectoral transformation be analyzed? To pursue these questions, it first presents selected approaches to the topic, followed by a pragmatic concept for analyzing technology- related sectoral transformation processes. – – Der Aufsatz geht der Frage nach, wie sich Wirtschaftssektoren unter dem Eindruck grundlegend neuer technologischer Möglichkeiten, die dort ein enormes Entwicklungsund Einsatzpotenzial haben, verändern und wie sich ein solcher sektoraler Wandel durch Technik analysieren lässt. Dazu werden zunächst ausgewählte Zugänge zum Thema vorgestellt und daran anschließend forschungspragmatische Überlegungen zur Untersuchung technikgeprägten sektoralen Wandels vorgestellt.
Keywords: 300